Optimizing Green Open Space Management as a Tourist Attraction: A Study of Bamboo Forest and Harmony Park in Surabaya - Ragilianty, Alvira Izza (Innovative: Journal Of Social Science Research, 2024)
This research aims also to study the application of GOS management in Surabaya as eco green tourism in the reference to bamboo forest and Harmony Park. This green area is urban green spaces and tourist attraction which potentially reduce pollutions provide recreational space and increase the quality of life of the resident community. This research is qualitative and uses the observation method, in-depth interviews, and document analysis. The key informants are field officers and managers of the park surrounding the Park Department of Hygiene and Green Open Space (DHGOS). The outcomes of the research demonstrate different DHGOS' in terms of green space management, such as behaviors of visitors who do not keep the environment clean, facilities that are damaged due to misuse, and limitations in financing for maintenance work. To overcome these challenges DHGOS utilizes sustainable greening projects, well-organized spaces, and regular facility & equipment monitoring & maintaining the facility & equipment. This management optimization is projected to strengthen the importance of bamboo forests and harmony parks as educational tourist items and sustainable green open spaces. The report suggests more visitor education and government assistance in finance as measures towards more successful green space management.